PEMANFAATAN TEKNOLOGI INFORMASI DALAM PEMBERIAN LAYANAN KONSELING INDIVIDUAL DI ERA DIGITAL - Firdha Ainil Hakim; Firman, Firman; Neviyarni, Neviyarni; Muhammad Asyraf Che Amat (Cahaya Ilmu Bangsa Institute, 2025)
Individual counseling services at the school aim to help students cope with personal, social, academic, and career issues. Through this service, students get direct attention from BK teachers to explore problems in depth and find solutions as needed. However, in its implementation, this service often faces problems, including low student interest in the importance of this service. Guidance and Counseling Management (BK) has a strategic role in increasing students' interest in participating in individual counseling services, especially in the digital era that is full of challenges and opportunities. This article was written after a literature study by analyzing various relevant scientific sources, including books and articles. Individual counseling services need to be optimized, starting from providing understanding related to counseling services, improving the ability of counselors to create a comfortable environment and utilizing technology in this digital era so that it can be effective and have a positive impact on overall student development.